Prevalence, Challenges in Diagnosis and Treatment of Non-Tuberculous Mycobacteria - Navidita Kangabam; Sneha S Hegadi; Divya C; Nethravathy V; KN Chidambara Murthy (Applied Microbiology: Theory ＆ Technology, 2025)
Mycobacteria that cause tuberculosis and Non-Tuberculous Mycobacteria (NTM) are the two groups into which mycobacteria are divided. Almost all the NTM are ubiquitous in soil, water, air, etc. During recent years, studies have suggested that they are now considered globally evolved emerging pathogens. The NTM infection can cause self limiting asymptomatic infections to life-threatening diseases, affecting multiple major organs. Several guidelines have been introduced for the treatment of pulmonary and extra-pulmonary NTM infections. Owing to its innate resistance, complexity, and resemblance of the organism to Mycobacterium Tuberculosis (MTB), the diagnosis and treatments have a high failure rate. Moreover, most healthcare workers lack knowledge of NTM infection, as the clinical symptoms and the microscopic morphology resemble MTB. This could lead to NTM becoming resistant to various antibiotics, and the treatment could become challenging in the future. This review article provides details on the prevalence of Tuberculosis (TB) and NTM in India and globally, information on the vulnerable population, complications caused, and means of diagnosis, treatment, and challenges associated with the diagnosis and treatment of NTM are discussed in detail. Additionally, information on various health complications associated with NTM and the challenges of NTM diagnosis is provided in detail. This article also throws light on co-infections associated with TB and NTM disease patterns that may lead to complications, along with treatment options for NTM are discussed in detail.